Religious freedom in a Democratic and Pluralistic Society: a Critical Appraisal of John Rawls Idea of Public Reason - N. Demaisip Bat-og, R. Vibekehh (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2018)
This paper presents a critical appraisal on John Rawls’ philosophy of public reason which presents some ambiguous and problematic issues that must be recognized and properly dealt with. There are three main objectives set forth in this paper. First, this presents key concepts of John Rawls’ idea of public reason as a means of dealing with different religious comprehensive doctrines that is in a way, beneficial to the interest of the state, second, this paper makes a philosophical and theoretical analysis of John Rawls’ idea of public reason, and third, this shows and illustrates some concrete examples of how John Rawls’ idea of public reason as a solution to conflicting religious comprehensive doctrines can appear rather problematic.Keywords: Religious Freedom, Democratic and Pluralistic Society, John Rawls